Quality and sensory assessment of honey sourced from different locations in Ibadan metropolis, Nigeria (2018)
Honey is a sweet food made by Bees using nectar from flowering plants. It is known to be subjected to various use: as direct edible and for pharmaceutical purposes. In Nigeria, particularly in Ibadan metropolis, the demand for honey is ever increasing due to the burgeoning population increase and also consequent to it nutritional and medicinal benefits. By the reason of the high demand of honey and low supply of the product, getting pure and original honey from the market is becoming very difficult, leading to some folks taking advantage of tire short fall thereby flooding the market with adulterated honey. It is however against this background that this study seeks to provide answers to the problem of identifying quality honey through proximate and sensory evaluation. Honey samples were obtained from three sources in Ibadan metropolis (UI, OO, and OJ) and analyzed for sensory and proximate properties such as fructose, sucrose. Maltose, glucose, moisture content, ash, protein, hydroxymethylfurfural (HMF), ascorbic acid, ether extract (fat), crude fibre, and nitrogen free extract (carbohydrate) content following Standard Association of Official Analytical Chemistry. The following range of values were determined for fructose, sucrose. Maltose, glucose, moisture content, ash, protein, hydroxymethylfurfural (HMF), ascorbic add, ether extract (fat), crude fibre, and nitrogen free extract range from 12.4-20.4, 5.0-7.7, 0.0- 0.17, 21.3-36.5, 23.3-36.6, 23.4-17.9, 0.50-0.26, 0.0-0.43, 7.4-7.6, 0.0-0.33, 0.0-0.23, 0.0-01, and 72.7-80.9, respectively. The three samples of honey are of good quality but OJ had the least. UI honey has the overall acceptability rating.